2023
DOI: 10.1002/nau.25147
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐Urethral and Anterior Vaginal Wall Masses: Does Radiological Imaging Change the Predicted Diagnosis?

Abstract: Introduction: This study aims to determine the accuracy of radiological imaging compared with surgical pathology in patients with periurethral (PU) and anterior vaginal wall (AVW) lesions.Methods: This study is a retrospective analysis of 126 women who underwent surgical treatment for PU and AVW masses between 2011 and 2020. Clinicopathological data were extracted along with radiological findings from medical records. The primary outcome was the diagnostic accuracy of preoperative imaging compared to the gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In these cases, imaging is recommended. Additionally, although experienced clinicians may be able to diagnose symptomatic periurethral and urethral lesions correctly up to 80% of the time, many find imaging to be helpful for the purposes of surgical planning and patient counseling [7 ▪▪ ]. For masses that are intermittent, it is important to perform imaging when the mass is present.…”
Section: Presentation and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, imaging is recommended. Additionally, although experienced clinicians may be able to diagnose symptomatic periurethral and urethral lesions correctly up to 80% of the time, many find imaging to be helpful for the purposes of surgical planning and patient counseling [7 ▪▪ ]. For masses that are intermittent, it is important to perform imaging when the mass is present.…”
Section: Presentation and Evaluationmentioning
confidence: 99%
“…In addition to being radiation-free like MRI, US is portable, can capture both static and dynamic images, is better tolerated by patients, and is cheaper than MRI. Recent studies have found US to be comparable to MRI in terms of diagnosis of urethral and periurethral female masses [4,7 ▪▪ ,10]. US is also the recommended imaging modality for assessment of midurethral sling location and function.…”
Section: Presentation and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation